Baligate : behind the scenes - Sudarman Asprianto (2008)
A study into Indonesia's biggest banking scandal, Baligate. Factors leading to the occurence of Baligate are examined. The report also links all the key events preceding Baligate. Finally, recommendations for IBRA to prevent the occurence of similar events are proposed.